2021
DOI: 10.1016/j.biomaterials.2020.120389
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting nanoparticulate DNase-1 for effective suppression of SARS-CoV-2-mediated neutrophil activities and cytokine storm

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a new strain of coronavirus not previously identified in humans. Globally, the number of confirmed cases and mortality rates of coronavirus disease 2019 (COVID-19) have risen dramatically. Currently, there are no FDA-approved antiviral drugs and there is an urgency to develop treatment strategies that can effectively suppress SARS-CoV-2-mediated cytokine storms, acute respiratory distress syndrome (ARDS), and sepsis. As symptoms progress in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
114
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(117 citation statements)
references
References 46 publications
0
114
0
Order By: Relevance
“…6). The results of this study revealed an improved survival in sepsis mouse model because of inhibited NETosis factors [224].…”
Section: Antiviral Therapy and Biomaterials For Drug Deliverymentioning
confidence: 59%
See 1 more Smart Citation
“…6). The results of this study revealed an improved survival in sepsis mouse model because of inhibited NETosis factors [224].…”
Section: Antiviral Therapy and Biomaterials For Drug Deliverymentioning
confidence: 59%
“…The surface of the PLGA nanoparticles was coated with polydopamine to immobilize DNase-1. Reproduced from[224], with permission from Elsevier…”
mentioning
confidence: 99%
“…Interaction between the viral spike (S) protein on the surface of the virus and the host receptor angiotensin-converting enzyme 2 (ACE2) on the surface of the target cell begins the process of viral entry inside host. ACE2 is a type I membrane receptor located across several cell types including endothelial cells of blood vessels, type II alveolar cells, small intestine enterocytes, and arterial smooth muscle cells of cerebral cortex, brainstem, and many organs (J. M. Kim et al, 2020). The S1 subunit of S contains a receptor binding domain (RBD) which binds to ACE2 6 for entry, and the binding is significantly enhanced by a single N501T mutation of ACE2, which indicates that screening for this mutation in populations can possibly determine proclivity to COVID-19 (Wan, Shang, Graham, Baric, & Li, 2020).…”
Section: Overview Of Sars-cov-2 Life Cyclementioning
confidence: 99%
“…Further, symptoms of sepsis like cytokine storm, organ damage, increase of NETs in organs and circulation are reflected in COVID-19 where increased circulating neutrophil levels predict a worse outcome (T. Chen et al, 2020;Guan et al, 2020;Veras et al, 2020). Moreover, Cit-histone H3 levels are increased in the plasma samples of COVID-19 patients with sepsis (Lee et al, 2020).…”
Section: The Link Between Histone Citrullination and Covid-19mentioning
confidence: 99%
“…In this regard, it has been proposed that the exogenous administration of recombinant DNase-1-coated nanoparticles or melanin-like nanospheres reduces ecDNA levels, neutrophil counts, and NETosis, ultimately modulating inflammation and lowering mortality [38,39].…”
Section: What Do We Know About Neutrophils During Covid-19?mentioning
confidence: 99%